Application of the bile duct tree concept in minimally invasive surgery for intrahepatic bile duct stones - LI Jingdong, HUANG Xujian, LI Qiang, ZHU Jianjiao (Waike lilun yu shijian, 2025)
Intrahepatic bile duct stones, as a prevalent disease in the field of hepatobiliary surgery in China, present multiple challenges in clinical management. The core factors contributing to stone retention and recurrence lie in the practical difficulties of implementing traditional anatomic hepatectomy and the limited efficacy in correcting biliary strictures. In response to this clinical dilemma, the specialty of biliary surgery has progressively developed a precise and minimally invasive resection concept guided by three-dimensional hepatic venous anatomy combined with lesioned bile duct tree distribution patterns. At the technical implementation level, it is imperative to establish a standardized operative system encompassing laparoscopic precision parenchymal transection, hilar bile duct plastic reconstruction, along with auxiliary techniques such as intraoperative ultrasound, indocyanine green fluorescence staining guidance, and multi-endoscopic combined stone extraction approaches.